2019
DOI: 10.1186/s12891-019-2978-1
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of bone marrow oedema at the sacroiliac joints in a non-rheumatological population — a retrospective cohort study

Abstract: BackgroundThe purpose of this study is to determine the incidence of bone marrow oedema (BME) at magnetic resonance imaging (MRI) of the sacroiliac joints (SIJ) in a non- rheumatological population, and to explore whether patient-reported outcome measures are suitable for predicting BME at the SIJ at referral. Furthermore, to investigate the final clinical diagnoses three months after initial SIJ MRI.MethodsThis study was a retrospective cohort study consisting of patients 18–45 years of age that were referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We detected significantly more frequent BME in patients with AAU compared to HS, which could be caused by the proportion of patients later diagnosed with axSpA, despite the fact that a subset of HS performed more regular sports activity than patients with AAU. The presence of BME at SIJ in healthy subjects was comparable to the incidence of BME at SIJ in the non-rheumatological population [ 23 ]. Highly suggestive BME was present only in patients with AAU; however, six patients without chronic back pain could not be classified as axSpA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We detected significantly more frequent BME in patients with AAU compared to HS, which could be caused by the proportion of patients later diagnosed with axSpA, despite the fact that a subset of HS performed more regular sports activity than patients with AAU. The presence of BME at SIJ in healthy subjects was comparable to the incidence of BME at SIJ in the non-rheumatological population [ 23 ]. Highly suggestive BME was present only in patients with AAU; however, six patients without chronic back pain could not be classified as axSpA.…”
Section: Discussionmentioning
confidence: 97%
“…BME on SIJ is the first and the most typical axSpA feature which can be found on MRI. However, BME lacks sufficient level of specificity due to its manifestation in other non-rheumatological and non-inflammatory conditions [ 23 ]. Therefore, integrating “highly suggestive” BME into the criteria for axSpA has been validated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nygaard et al [9] showed that the mean age of the population was 33.1 years of age (standard deviation (SD): 7.89), The groups primarily consisted of women in both groups…”
Section: Discussionmentioning
confidence: 99%